The Difference in the Effectiveness of Removing the Modern Super Ring Circumcision Device with Olive Drops and Aloe Vera Ointment Treatment - Sutrisno; Taufiq Abdullah; Mayta Sari Dwianggimawati (Universitas STRADA Indonesia, 2024)
Background: Circumcision using the Super Ring method requires removing the ring after the wound is dry by treating used the principle of moisture. Purpose: The aim of this study was to determine the difference in the effectiveness of removing the Modern Super Ring Circumcision Device with Olive Drops and Aloe vera Ointment treatment. Method: The research design used Pre-Experimental with a post test only approach, used Accidental Sampling with a research sample of 32 respondents and tested using the Mann Whitney test. The majority of 14 respondents (87.4%) removed the circumcision ring with aloe vera ointment treatment in less than 10 days, while the majority of 15 respondents (93.7%) received circumcision ring removal with olive drops in more than 10 days. Results: The results of the Mann Whitney Test obtained a p value of 0.000, indicating that there was a significant difference, aloe vera ointment showed that the average time required to remove the Circumcision Ring was faster than olive drops. Conclusion: Aloe vera ointment made the wound environment more moist, thereby speeding up the wound healing process.